Răspuns :
a) 91- (48 : 6 + 7 * 6) = 91 - (8 + 42) = 91 - 50 = 41
b) 19 + (9 * 7 - 49 : 7 - 28 : 7) = 19 + (63 - 7 - 4) = 19 + 52 = 71
c) 36 + (63 : 7 + 36 : 6 - 21 : 7) = 36 + (9 + 6 - 3) = 36 + 12 = 48
b) 19 + (9 * 7 - 49 : 7 - 28 : 7) = 19 + (63 - 7 - 4) = 19 + 52 = 71
c) 36 + (63 : 7 + 36 : 6 - 21 : 7) = 36 + (9 + 6 - 3) = 36 + 12 = 48
91-(48:6+7×6)=
91-(8+42)=
91-50=41
19+(9×7-49:7-28:7)=
19+(63-7-4)=
19+52=71
36+(63:7+36:6-21:7)=
36+(9+6-3)=
36+12=48
91-(8+42)=
91-50=41
19+(9×7-49:7-28:7)=
19+(63-7-4)=
19+52=71
36+(63:7+36:6-21:7)=
36+(9+6-3)=
36+12=48